Comparative Evaluation of Water Sorption and Surface Roughness in Acrylic Denture Bases Fabricated by Conventional and CAD/CAM Techniques - Mina Mohaghegh; Elham Ansarifard; Fateme Erfanizade; Masume Taghva; Zahra Pouladi (Journal of Mashhad Dental School)
Background: The acrylic denture base must exhibit minimal water sorption and surface roughness to ensure comfort, aesthetics, oral health, dimensional stability, and strength. This study aimed to compare the surface roughness and water sorption properties of acrylic denture bases fabricated using conventional and CAD/CAM techniques.Methods and Materials: In this in-vitro study, a total of 24 specimens were prepared in disk form (21 mm in diameter and 2.5 mm in thickness). Two sample groups were compared (n=12): heat-cured acrylic resins and CAD/CAM milled acrylic resin. Surface roughness values (Ra) were measured using a contact profilometer before and after polishing. Measurements were conducted at three points and an average value was calculated for each sample. For water sorption assessment, samples were first kept in a desiccator for 24 hours and then the dimensional measurements were recorded using a digital caliper. The samples were immersed in physiological serum and incubated at 37°C and weighed daily until reaching a constant weight, followed by desiccation and daily weighing to determine final constant weight. Water sorption was calculated and reported in µg/cm3. The data was analyzed using Independent samples T-test. The significance level was set at P-value≤0.05.Result: The average Ra values were significantly lower in the CAD/CAM group compared to the heat-cured group before and after surface polishing (P<0.001 and P=0.003, respectively). Similarly, CAD/CAM milled samples demonstrated significantly lower water sorption rates compared to heat-cured specimens (P<0.001).Conclusion: The CAD/CAM acrylic dentures exhibited smoother surfaces and lower water sorption rates compared to heat-processed acrylic dentures, making them a more effective choice for denture fabrication.